Hybrid traction system for diesel trains - Neshcheret, Volodymyr (National Technical University "Kharkiv Polytechnic Institute", 2024)
The article analyzes improving the traction and energy performance of diesel motor-car rolling stock. It is determined that a significant improvement can be achieved by using hybrid traction systems.
Keywords: hybrid traction systems; energy efficiency; rolling stock; energy performance; diesel trains; suburban transportation